Impact of Interprofessional Simulation on Teamwork Performance Amongst Medical and Nursing Students at the University of Algarve - Michael Isidro, Alexandra Binnie, André Correia, Manuela Castro, Conceição Farinha, Helena José (Journal of the Portuguese Society of Anesthesiology, 2024)
Impact of Interprofessional Simulation on Teamwork Performance Amongst Medical and Nursing Students at the University of Algarve